PENGARUH KINERJA KEUANGAN, GOOD CORPORATE GOVERNANCE, STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN TBK - Virliana Putri Rosadi; Trisa Indrawati (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine and analyze the effect of financial performance, good corporate governance, capital structure and company growth.Data analysis was carried out using statistics with SPSS tools. Based on the results of the analysis using the t test, it is known that partially financial performance and good corporate governance have a significant effect on firm value. Meanwhile, the variables of capital structure and company growth have no effect on firm value. Furthermore, based on the results simultaneously using the F test, it is known that simultaneously financial performance, good corporate governance, capital structure and company growth have an effect on firm value. Thus, it is advisable for companies to pay attention to the condition of financial performance, good corporate governance, capital structure and company growth so that company value is maintained.